Pathways to Formalization : Going Beyond the Formality Dichotomy -- The Case of Peru - Díaz, Juan José (World Bank, Washington, DC, 2018)
Too often, academics and policy makers interpret formality as a binary choice and formalization as an irreversible process. Yet, formalization has many facets and shades on the business and labor fronts, and firms may not be able or willing to formalize all at once. This paper explores the joint process of business and labor formalization, using a unique panel data set of Peruvian micro enterprises. The paper finds that business formality does not imply labor formality, and vice versa. Further, there is significant churning in and out of different dimensions of formality within a relatively short period. Using an instrumental variable approach, the paper infers that business formalization affects labor formalization but not the other way around, and that enforcement is a key driver of formalization. Overall, the analysis shows that formalization is a gradual and reversible process, with small entrepreneurs weighing their possibilities in each pathway to business (often) or labor (less often) formalization, but rarely both at the same time.